Idea on the Clinical Services of Primary Care Physicians - Adi Heru Sutomo; Fitriana Fitriana (Faculty of Medicine, Public Health, and Nursing, 2018)
The increasing needs and health problems that exist in the community and the more critical the community-related health problems that require the ability of a primary care doctor able to handle existing health problems in the community. Primary care doctor complies with Alma Ata Declaration in 1978 as the backbone of health that makes direct contact with the community, so it is essential for a primary care doctor to involve the patient or the patient as part of the team. Patient experience information or patients given to primary care doctors is expected to further improve the quality of patient health services as individuals and is part of the family and society or community....................